Sistem Informasi Laporan Asset Fakultas Teknologi Komunikasi dan Informatika Universitas Nasional - Rifqi Firmansyah; Septi Andryana; Benrahman Benrahman (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Current technological developments, in reporting assets in the Faculty of Communication and Information Technology of the National University have not been effective. Because the many assets that exist make it difficult for workers to recapitalize the asset report. Such as incoming and outgoing asset reports and asset status status. Therefore, the Web-based National University Faculty of Communication and Information Technology Asset Report Information System was designed so that workers could report asset data every month. Application trial results for reporting asset data, the system can display the report results based on incoming assets, outgoing assets, and asset status with 100% accuracy. In the search for asset data entered the system can display the results of the report based on the transaction id, date of asset entered, and the name of the asset with 100% accuracy. Then to report asset data out the system can display the results of the report based on the transaction id, exit, and the name of the asset with 100% accuracy